2019
DOI: 10.1063/1.5093040
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer turbulence and freestream turbulence interface, turbulent spot and freestream turbulence interface, laminar boundary layer and freestream turbulence interface

Abstract: We study the boundary-layer turbulence and freestream turbulence interface (BTFTI), the turbulent spot and freestream turbulence interface (TSFTI), and the laminar boundary-layer and freestream turbulence interface (LBFTI) using direct simulation. Grid spacings in the freestream are less than 1 Kolmogorov length scale during transition. Probability density functions of temperature and its derivatives are used to select the interface identification threshold, corroborated by a vorticity-based method. The interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
5
22
0
Order By: Relevance
“…Kozul et al (2020) explicitly compared their instantaneous structure to that of Hancock & Bradshaw (1989) and found qualitatively good agreement, however, the main focus of their study was the statistics of the temporal boundary layer subject to a sudden injection of FST. The DNS studies of You & Zaki (2019) and Wu et al (2019) roughly echo these results, however, they investigate only a single FST case at limited Reynolds numbers. This is understandable as it is computationally expensive to compare multiple cases and achieve higher Reynolds numbers.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Kozul et al (2020) explicitly compared their instantaneous structure to that of Hancock & Bradshaw (1989) and found qualitatively good agreement, however, the main focus of their study was the statistics of the temporal boundary layer subject to a sudden injection of FST. The DNS studies of You & Zaki (2019) and Wu et al (2019) roughly echo these results, however, they investigate only a single FST case at limited Reynolds numbers. This is understandable as it is computationally expensive to compare multiple cases and achieve higher Reynolds numbers.…”
Section: Introductionmentioning
confidence: 64%
“…Moreover, the TBL experiments of Laskari et al (2018) detected UMZs beneath a freestream of approximately 3 % turbulence. Finally, the recent study of Wu et al (2019) also identified an instantaneous separation between the freestream and the wall-bounded flow in DNS of a zero-pressure-gradient TBL. Thus, UMZs exist in flows with turbulence in the freestream, and the flow may be separated into the flow directly influenced by the wall and the turbulent flow in the freestream or core.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, our DNS profiles for the rate of viscous dissipation of turbulent kinetic energy ε + = ε/(u 4 τ /ν) as a function of y + are in excellent agreement, not only in slope but also in intercept, over the logarithmic region, with the asymptotic theoretical relation ε + = 1/(κy + ). Further details about the ZPGSFPBL simulation can be found in Wu, Wallace & Hickey (2019).…”
Section: Flow Cases Consideredmentioning
confidence: 99%